2003
DOI: 10.1109/tgrs.2002.808065
|View full text |Cite
|
Sign up to set email alerts
|

Lithologic characterization of a reservoir using continuous-wavelet transforms

Abstract: | We consider the problem of characterizing the lithology of a reservoir using gamma ray logs as well as seismic traces around the well. We rst calculate the continuous wavelet transform of the the data and then use the fact that the energy of such transformation is proportional to a power of its scale. The technique consists in estimating the power transformation obtaining a set of values of the same size as the original data and then model the distribution of these values using a double exponential. We nd th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 17 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…used the WTs to analyze the porosity logs. Alvarez et al (2003) characterized the lithology of a reservoir using the GR log and seismic traces around wells. By calculating the wavelet coefficients and the "energy" of the WTs, they showed that the wavelet energy distributions of the wells in sandstones were significantly different from those of the wells in gravel.…”
Section: Introductionmentioning
confidence: 99%
“…used the WTs to analyze the porosity logs. Alvarez et al (2003) characterized the lithology of a reservoir using the GR log and seismic traces around wells. By calculating the wavelet coefficients and the "energy" of the WTs, they showed that the wavelet energy distributions of the wells in sandstones were significantly different from those of the wells in gravel.…”
Section: Introductionmentioning
confidence: 99%
“…Rabiller et al (2003) used signal processing methods in order to speed up log data interpretations in the framework of sequence stratigraphy and sedimentary bodies' architecture while improving their consistency by minimizing any possible operator bias. Alvarez et al (2003) characterized lithologic properties of a reservoir using wavelet transform. Their method is based on an estimation of the power energy coefficient of signals corresponding to gamma ray logs as well as seismic traces penetrating the rock.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several techniques of spectral analyses (Fourier, Walsh, wavelet transforms) and fractal theory have been applied to solve the various geophysical problems. For instance, (i) log analysis (Doveton 1986;Pan et al 2008), (ii) reservoir characterization (Alvarez et al 2003), (iii) climate signal detection (Lau and Weng 1995), (iv) chemical analysis (Leung et al 1998), and (v) conjunction model for groundwater level forecasting (Adamowski and Chan 2011). KTB research geoscientist team has examined the fractal behaviour of well-log signal variability, presuming that well-log signals in the super deep German Continental Deep Drilling Program (KTB) borehole display nonlinear characteristics (Leonardi and Kumpel 1999).…”
Section: Introductionmentioning
confidence: 99%